PROPORTIONAL MORTALITY RATIO DUE TO CHAGAS DISEASE IS FIVE TIMES HIGHER FOR THE STATE OF GOIAS THAN THE REST OF BRAZIL - Alves Moraes, Cicílio; Ostermayer Luquetti, Alejandro; Gonçalves Moraes, Patrícia; Gonçalves de Moraes, Cristiane; Elisabeth Campos Oliveira, Dayse; Chaves Oliveira, Enio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Mortality data due to Chagas disease for the endemic State of Goias, Brazil, was retrieved from the National System of Information on Mortality, between 2006 and 2011. A total of 29,041 deaths were attributed to Chagas disease in the country, of which 4,293 (14.8%) occurred in the State of Goias. The proportion of deaths attributable to Chagas disease was 0,4% for the country overall and 2.4% for State of Goias. Seventy-two percent of the records were from individuals over 60 years of age, and heart disease was the main cause of death in 80.3%. Chagas disease is a major cause of death in Goias and, proportionally, 5.3 times higher than for the rest of the country.